LEGAL CERTAINTY REGARDING COLLECTION RELATED TO GUARANTEES IN TERMS OF MOTOR VEHICLE FINANCING BASED ON OJK REGULATION NO. 22 OF 2023 - Purba, Kevin Agatha; Harjono, Dhaniswara K.; Panjaitan, Hulman (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
One form of law that has a real and important role in people's lives is contract law. The term "contract" is called "overeenkomst" in Dutch and "agreement/agreement" in English. An agreement is defined in Article 1313 of the Civil Code, which states "An agreement is an act by which one or more people bind themselves to one or more other people". Contract law can be said to be a law that is formed when someone promises something to another person. In this case, both parties have agreed to enter into an agreement without any enforcement or decision by only one party. The type of research is normative legal research. Normative law, there are several approaches in this legal study. In this approach, the authors receive information from various aspects of the problem they want to find answers to. Conclusion: Restructuring of motorcycle consumer protection agreements in financial companies. In essence, Regulation 22/2023 was issued to further strengthen consumer protection in the financial services sector by facilitating coordination of PUJK internal control. In this case, the new framework is expected to guarantee.